A year-round analysis of railway station overruns due to low adhesion conditions. (April 2023) - White, Ben; Watson, Mike; Lewis, Roger
Key Performance Indicators, such as station overruns and delay minutes, are used to assess the performance and punctuality of the GB railway. They can be used to quantify the effects of low adhesion, but the majority of previous analysis has been constrained to the autumn season. A Python script has been created in this work to extract 11 years of detailed passenger and freight station overrun data, throughout the entire year. The information gathered includes time and date, location, direction, vehicle type, railhead conditions and subsequent delay minutes caused by the incident. Although the majority of low adhesion related overruns occur in the autumn season due to leaf fall, this work has highlighted the number of low adhesion related issues that occur throughout the year where there are no visible signs of contamination. This work gives an overview of this new dataset and looks at some key trends in the data but the granular detail available means that future case studies could be carried out in specific locations, linked to geographic and meteorological data, to assess when and why low adhesion is occurring. From an operational perspective, the dataset could then be used as a daily updated assessment of the effectiveness of low adhesion mitigation methods.